The Effect of High-Intensity Intermittent Exercise on Body Composition of Overweight Young Males. (6th June 2012) - Heydari, M.; Freund, J.; Boutcher, S. H.
Abstract : To determine the effect of a 12-week high intensity intermittent exercise (HIIE) intervention on total body, abdominal, trunk, visceral fat mass, and fat free mass of young overweight males. Participants were randomly assigned to either exercise or control group. The intervention group received HIIE three times per week, 20 min per session, for 12 weeks. Aerobic power improved significantly (P < 0.001 ) by 15% for the exercising group. Exercisers compared to controls experienced significant weight loss of 1.5 kg (P < 0.005 ) and a significant reduction in total fat mass of 2 kg (P < 0.001 ). Abdominal and trunk adiposity was also significantly reduced in the exercising group by 0.1 kg (P < 0.05 ) and 1.5 kg (P < 0.001 ). Also the exercise group had a significant (P < 0.01 ) 17% reduction in visceral fat after 12 weeks of HIIE, whereas waist circumference was significantly decreased by week six (P < 0.001 ). Fat free mass was significantly increased (P < 0.05 ) in the exercising group by 0.4 kg for the leg and 0.7 kg for the trunk. No significant change (P > 0.05 ) occurred in levels of insulin, HOMA-IR, and blood lipids. Twelve weeks of HIIE resulted in significant reductions in total, abdominal, trunk, and visceral fat and significant increases in fat free mass and aerobic power.